Muslims in France: Identifying a discriminatory equilibrium - Claire L. Adida; David D. Laitin; Marie-Anne Valfort (Institute for the Study of Labor (IZA), 2012)
We analyze the assimilation patterns of Muslim immigrants in Western countries with a unique identification strategy. Survey and experimental data collected in France in 2009 reveal that Muslims and rooted French are locked in a sub-optimal equilibrium whereby (i) rooted French exhibit taste-based discrimination against those they are able to identify as Muslims and (ii) Muslims perceive French institutions as systematically discriminatory against them. This equilibrium is sustained because Muslims, perceiving discrimination as institutionalized, are reluctant to assimilate and rooted French, who are able to identify Muslims as such due to their lower assimilation, reveal their distaste for Muslims.
Keywords: C90; D03; J15; J71; Z12; 330; assimilation; Muslim and Christian immigrants; discrimination; France; Muslime; Soziale Integration; Ethnische Beziehungen; Ethnische Diskriminierung; Frankreich